2003
DOI: 10.1074/jbc.m208080200
|View full text |Cite
|
Sign up to set email alerts
|

Specific Nitration at Tyrosine 430 Revealed by High Resolution Mass Spectrometry as Basis for Redox Regulation of Bovine Prostacyclin Synthase

Abstract: Treatment of bovine aortic microsomes containing active prostacyclin synthase (PGI 2 synthase) with increasing concentrations of peroxynitrite (PN) up to 250 M of PN yielded specific staining of this enzyme on Western blots with antibodies against 3-nitrotyrosine (3-NT), whereas above 500 M PN staining of additional proteins was also observed. Following treatment of aortic microsomes with 25 M PN, PGI 2 synthase was about halfmaximally nitrated and about half-inhibited. It was then isolated by gel electrophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 43 publications
3
107
0
3
Order By: Relevance
“…Whereas many enzymes are subject to inhibition by peroxynitrite, the contribution of tyrosine nitration, S-nitrosation, and other mechanisms to inactivation varies considerably [67][68][69][70]. DTT only partially protected against PDHC inhibition, suggesting that tyrosine nitration is the primary mechanism of inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas many enzymes are subject to inhibition by peroxynitrite, the contribution of tyrosine nitration, S-nitrosation, and other mechanisms to inactivation varies considerably [67][68][69][70]. DTT only partially protected against PDHC inhibition, suggesting that tyrosine nitration is the primary mechanism of inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Our previous studies 20,21 demonstrated that ONOO ÏȘ selectively nitrates tyrosine 450, a residue situated in the active site of PGIS. To assay whether CD40L inhibits PGIS by tyrosine nitration of the enzyme, PGIS proteins were first immunoprecipitated with a polyclonal antibody against PGIS and were further stained for a monoclonal antibody against 3-NT in Western blots.…”
Section: Davis and Zoumentioning
confidence: 99%
“…15,16 Using normal aortic vessel strips, we have subsequently shown that ONOO ÏȘ exposure leads to nitration of PGIS, associated with impaired PGI 2 production, and a defective vasorelaxation. 19 The underlying mechanism for PGIS blockade has been suggested as the nitration of tyrosine 430 at the active site 20 through a reaction catalyzed by the ferric iron of this heme-thiolate (P450) protein. 21 In spite of the cellular antioxidant potential, ONOO ÏȘ causes PGIS nitration in whole cells 13,22 and in intact coronary arteries.…”
Section: Clinical Perspective P 2192mentioning
confidence: 99%
“…Tandem mass spectra acquired on quadrupole-time of flight instruments were averaged for at least one minute, whereas at least five scans were averaged on the triple quadrupole instrument, depending on the peptide concentration. FT-ICR tandem mass spectra were obtained by collecting 16 single scans using experimental conditions as described [26]. For the calibration plot, potential differences were stepped by 2 V with an acquisition time of 15 s per increment for each of the 22 precursor ions.…”
Section: Mass Spectrometrymentioning
confidence: 99%